Immunoglobulin gene rearrangements and mutational status in argentinian patients with chronic lymphocytic leukemia - Stanganelli, Carmen Graciela (2013)
Background: Chronic lymphocytic leukemia (CLL) is a clinically heterogeneous disease. The mutational status of the immunoglobulin heavy chain variable (IGHV) region represents one of the best prognostic markers and defines 2 disease subgroups: mutated (M-CLL) and unmutated (UM-CLL), with different clinical course. Materials and Methods: IGHV-D-J gene rearrangements and mutational status were analyzed in 73 Argentinian patients with CLL, 22 previously treated, by reverse transcriptase-polymerase chain reaction and bidirectional sequencing. The results were compared with those reported in other geographic regions. Fluorescence in situ hybridization analysis was also performed. Results: A total of 43 (58.9%) cases were of patients with M-CLL, and 30 (41.1%) were patients with UM-CLL. Deletion of chromosome 13q14 as a single alteration was more frequently observed in the M-CLL group (48%) than in the UM-CLL group (24%). In the M-CLL group, the proportion of cases with deletion of chromosome 13q14 was significantly higher than those with +12 and those with deletions of chromosomes 17p and 11q (P =.003). The most frequently used IGHV families were IGHV3 > IGHV1 > IGHV4, which are different from those observed in Asian, Brazilian, and Uruguayan series. The IGHV3-23 gene (10.8%) was the most commonly used, followed by IGHV1-69 (9.5%), IGHV4-59 and IGHV2-5 (6.8% each), and IGHV3-21 and IGHV3-30 (5.4% each). IGHV4-34 showed the lowest frequency (2.7%) in our cohort compared with published data, whereas IGHV4-59, IGHV3-72, and IGHV2-5 were overexpressed in our series. Stereotyped HCDR3 (heavy chain complementary determining region 3) was found in 9.5% of patients. Conclusions: Our results showed that Argentinian patients with CLL display an IGHV gene usage that resembles that observed in Western countries and exhibited interesting similarities and differences with respect to published series from other Latin American populations, which reflect variations in the genetic background.